Linear high resolution dust mass spectrometer for a mission to the Galilean satellites - Kempf, Sascha; Srama, Ralf; Grün, Eberhard; Postberg, Frank (Planetary and space science, 2012)
The discovery of volcanic activity on Enceladus stands out amongst the long list of findings by the Cassini mission to Saturn. In particular the compositional analysis of Enceladus ice particles by Cassini's Cosmic Dust Analyser (CDA) (Srama et al., 2004) has proven to be a powerful technique for obtaining information about processes below the moon's ice crust. Small amounts of sodium salts embedded in the particles' ice matrices provide direct evidence for a subsurface liquid water reservoir, which is, or has been, in contact with the moon's rocky core (Postberg et al., 2009, Postberg et al., 2011b). Jupiter's Galilean satellites Ganymede, Europa, and Callisto are also believed to have subsurface oceans and are therefore prime targets for future NASA and ESA outer Solar System missions. The Galilean moons are engulfed in tenuous dust clouds consisting of tiny pieces of the moons' surfaces (Krüger et al., 1999), released by hypervelocity impacts of micrometeoroids, which steadily bombard the surfaces of the moons. In situ chemical analysis of these grains by a high resolution dust spectrometer will provide spatially resolved mapping of the surface composition of Europa, Ganymede, and Callisto, meeting key scientific objectives of the planned missions. However, novel high-resolution reflectron-type dust mass spectrometers (Sternovsky et al., 2007, Srama et al., 2007) developed for dust astronomy missions (Grün et al., 2009) are probably not robust enough to be operated in the energetic radiation environment of the inner Jovian system. In contrast, CDA's linear spectrometer is much less affected by harsh radiation conditions because its ion detector is not directly facing out into space. The instrument has been continuously operated on Cassini for 11 years. In this paper we investigate the possibility of operating a CDA-like instrument as a high resolution impact mass spectrometer. We show that such an instrument is capable of reliably identifying traces of organic and inorganic materials in the ice matrix of ejecta expected to be generated from the surfaces of the Galilean moons. These measurements are complementary, and in some cases superior, compared to other traditional techniques such as infrared remote sensing or in situ ion or neutral mass spectrometers.